Maternal and infant pregnancy outcomes in women with psoriatic arthritis: a Swedish nationwide cohort study. (3rd July 2019) - Remaeus, K; Stephansson, O; Johansson, K; Granath, F; Hellgren, K
Abstract : Objective: Studies on pregnancy outcomes in psoriatic arthritis (PsA) are scarce and typically of small size. Available studies have reported conflicting results. The aim of this study was to describe maternal and infant pregnancy outcomes among women with PsA compared with women without PsA. Design: Nationwide cohort study. Setting: Nationwide Swedish registers. Population: A total of 41 485 singleton pregnancies in 1997–2014, of which 541 pregnancies were identified with PsA exposure and 40 944 pregnancies were unexposed. Methods: By linkage of national health and population register data, we obtained information on individual pregnancies and compared outcomes among pregnancies with PsA and non‐PsA pregnancies. Relative risks were estimated by odds ratios (ORs) with 95% CIs using a generalised linear regression model with generalised estimating equations. Adjustments were made for maternal factors and calendar year of birth. Main outcome measures: Maternal and infant pregnancy outcomes. Results: Pregnancies to women with PsA had increased risks of preterm birth (adjusted OR 1.63; 95% CI 1.17–2.28), elective and emergency caesarean deliveries (adjusted OR 1.47; 95% CI 1.10–1.97 and adjusted OR 1.43; 95% CI 1.08–1.88, respectively) compared with non‐PsA pregnancies. No increased risks were observed for pre‐eclampsia, stillbirth or other infant outcomes apart from preterm birth. Conclusion: The majority of women with PsA have uneventful pregnancies with respect to adverse outcomes. In the present study, we found increased risks of preterm birth and caesarean delivery compared with non‐PsA pregnancies. Tweetable abstract: Women with psoriatic arthritis have uneventful pregnancies but are at increased risk of preterm birth and caesarean delivery. Tweetable abstract: Women with psoriatic arthritis have uneventful pregnancies but are at increased risk of preterm birth and caesarean delivery.